Heat shrinkable tube at high speed in low temperature

KR103021591B1Active Publication Date: 2026-09-18LS CABLE LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020210041569
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-03-31
Publication Date
2026-09-18
Estimated Expiration
2041-03-31

Smart Images

  • Figure 112021037616268-PAT00005_ABST
    Figure 112021037616268-PAT00005_ABST
Patent Text Reader

Abstract

The present invention relates to a heat shrink tube capable of high-speed shrinkage at low temperatures. Specifically, the present invention relates to a heat shrink tube capable of high-speed shrinkage at low temperatures, as well as having excellent physical properties such as mechanical properties, heat resistance, and flame retardancy, and enabling a reduction in manufacturing costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a heat shrink tube capable of high-speed shrinkage at low temperatures. Specifically, the present invention relates to a heat shrink tube capable of high-speed shrinkage at low temperatures, as well as having excellent physical properties such as mechanical properties, heat resistance, and flame retardancy, and enabling a reduction in manufacturing costs. Background Technology

[0002] Heat shrink tubes are tubes that shrink in diameter or length when hardened after heating. They are widely used for packaging, such as by hermetically covering connections of insulated wires or conduits, or by fitting them onto the inner surfaces of bottles or batteries.

[0003] With this heat shrink tube, a product or part to be coated or packaged is inserted into the hollow portion of the heat shrink tube, and by keeping them at an appropriate temperature, the heat shrink tube shrinks and comes into close contact with the product or part placed inside the hollow portion.

[0004] Conventionally, the residence temperature for shrinking heat shrink tubes was high, exceeding 170°C, and there was a problem in that it was difficult to use with products that were at risk of decomposition or deformation at high temperatures above 170°C. For example, in the case of heat shrink tubes for automotive wire harnesses, a problem occurs where the wire sheath material melts when it is held at high temperatures above 170°C.

[0005] For this reason, there is a need for heat-shrinkable tubes capable of shrinking even at low temperatures. Although there have been instances where the resin included in the composition for heat-shrinkable tubes was modified to lower the shrinkage temperature of conventional heat-shrinkable tubes, heat-shrinkable tubes manufactured from compositions containing such modified resins suffered from problems such as reduced mechanical properties, heat resistance, and flame retardancy.

[0006] Meanwhile, although research has been conducted to reduce the shrinkage time required for heat shrink tubes by controlling the degree of crosslinking, filler content, and modulus, there were limitations in shortening the shrinkage time solely by adjusting these modulus values ​​because it is difficult to accurately identify the factors affecting the shrinkage of heat shrink tubes; furthermore, it was confirmed that increasing the filler content leads to increased manufacturing costs.

[0007] Therefore, there is an urgent need for heat-shrinkable tubes that not only allow for high-speed shrinkage at low temperatures but also possess excellent physical properties such as mechanical characteristics, heat resistance, and flame retardancy, while reducing manufacturing costs. The problem to be solved

[0008] The present invention aims to provide a heat shrink tube capable of shrinking at high speed at low temperatures.

[0009] In addition, the present invention aims to provide a heat shrink tube that has excellent physical properties such as mechanical properties, heat resistance, and flame retardancy, and can reduce manufacturing costs. means of solving the problem

[0010] To solve the above problem, the present invention,

[0011] A heat shrink tube is provided comprising ethylene vinyl acetate (EVA) resin and polyethylene (PE)-based resin as base resins, wherein the ethylene vinyl acetate (EVA) resin has a melting point (Tm) of 72 to 98°C, the polyethylene (PE)-based resin has a melting point (Tm) of 100 to 120°C, and the 2% secant modulus is 20,000 to 25,000 psi.

[0012] Herein, a heat shrink tube is provided, characterized in that the content of vinyl acetate (VA), which is a comonomer of the ethylene vinyl acetate (EVA) resin, is 4.5 to 28 weight% based on the total weight of the ethylene vinyl acetate (EVA) resin.

[0013] In addition, the present invention provides a heat shrink tube characterized by comprising a low-density polyethylene (LDPE) resin having a melting point (Tm) of 100 to 110°C and a linear low-density polyethylene (LLDPE) resin having a melting point (Tm) of 105 to 120°C.

[0014] In addition, the present invention provides a heat shrink tube characterized in that the linear low-density polyethylene (LLDPE) resin comprises a linear low-density polyethylene (m-LLDPE) resin polymerized under a metallocene catalyst.

[0015] Herein, a heat shrink tube is provided, characterized in that the weight ratio of the low-density polyethylene (LDPE) resin and the linear low-density polyethylene (m-LLDPE) resin polymerized under the metallocene catalyst is 1:3 to 3:1.

[0016] Meanwhile, a heat shrink tube is provided, characterized in that the weight ratio of the ethylene vinyl acetate (EVA) resin and the polyethylene (PE) resin is 4:6 to 6:4.

[0017] In addition, a heat shrink tube is provided, characterized by comprising 25 to 34 parts by weight of a bromine-based flame retardant and 12 to 17 parts by weight of an antimony-based flame retardant based on 100 parts by weight of the base resin.

[0018] Furthermore, a heat shrink tube is provided, characterized by comprising 2 to 5 parts by weight of a crosslinking agent of trimethylopropane trimethacrylate or triaryl isocyanurate based on 100 parts by weight of the base resin.

[0019] In addition, the present invention provides a heat shrink tube characterized by comprising, based on 100 parts by weight of the base resin, 0.5 to 5 parts by weight of a lubricant, and 7 to 15 parts by weight of one or more other additives selected from the group consisting of an antioxidant, a hydrolytic agent, carbon black, a UV inhibitor, a processing aid, a heat stabilizer, an antistatic agent, a coupling agent, and a pigment. Effects of the invention

[0020] The heat shrink tube according to the present invention exhibits an excellent effect of being able to shrink at high speed at low temperatures by controlling the type of base resin and the melting point based on the correlation between the type of base resin and the melting point and the start time of shrinkage.

[0021] In addition, the heat-shrink tube according to the present invention exhibits excellent physical properties such as mechanical properties, heat resistance, and flame retardancy by precisely controlling the type and content of the base resin and filler, and demonstrates the excellent effect of reducing manufacturing costs. Brief explanation of the drawing

[0022] FIG. 1 schematically illustrates the cross-sectional structure of a heat shrink tube according to one embodiment of the present invention. FIG. 2 schematically illustrates the cross-sectional structure of a heat shrink tube according to another embodiment of the present invention. Specific details for implementing the invention

[0023] Hereinafter, preferred embodiments of the present invention will be described in detail. However, the present invention is not limited to the embodiments described herein and may be embodied in other forms. Rather, the embodiments introduced herein are provided to ensure that the disclosed content is thorough and complete, and to ensure that the spirit of the present invention is sufficiently conveyed to those skilled in the art. Throughout the specification, the same reference numerals indicate the same components.

[0024] Figures 1 and 2 schematically illustrate the cross-sectional structure of a heat shrink tube according to the present invention.

[0025] As illustrated in FIG. 1, the heat shrink tube (100) according to the present invention may have a cylindrical structure having a hollow portion (110) into which a product or part to be coated or packaged therefrom is inserted and disposed, and the thickness, inner diameter, outer diameter, etc. may vary depending on the application and environment in which the heat shrink tube is applied. In addition, as illustrated in FIG. 2, the heat shrink tube (100) may have a structure in which an adhesive coating layer (120) is provided on the inner wall.

[0026] The inventors confirmed through Differential Scanning Calorimetry (DSC) and Thermomechanical Analysis (TMA) that the melting point at which chain relaxation of the polymer resin included in the heat shrink tube occurs and the temperature at which shrinkage of the heat shrink tube begins are similar. Therefore, by controlling the melting point (Tm) of the polymer resin to a lower level, the shrinkage initiation temperature of the heat shrink tube can be lowered. By experimentally confirming that high-speed shrinkage at low temperatures is possible, which was previously limited by studies aimed simply at improving shrinkage speed, the present invention was completed.

[0027] In addition, since the thermal conductivity of polymer resins is very low, at about one-fourth the level of metals, it was conventionally possible to use an excessive amount of filler to achieve rapid heat conduction in order to quickly reach the temperature at which chain relaxation begins in the shrinkage mechanism of the heat shrink tube containing the polymer resin. However, in such cases, the mechanical properties, heat resistance, and flame retardancy of the heat shrink tube may be reduced. Therefore, to maintain these physical properties, the use of an excessive amount of filler was excluded, and at the same time, the 2% secant modulus of the heat shrink tube was adjusted to 20,000 psi or higher, for example, 20,000 to 25,000 psi, to achieve semi-rigid properties, thereby securing mechanical properties while controlling the melting point (Tm) to a low level, thereby enabling high-speed shrinkage of the heat shrink tube at low temperatures.

[0028] If the above 2% secant modulus value is less than 20,000 psi, the hardness of the product is insufficient, and it may be excessively vulnerable to external impacts and scratches; if it exceeds 25,000 psi, shrinkage characteristics are reduced and workability decreases due to high hardness.

[0029] In particular, the heat shrink tube according to the present invention may be capable of complete shrinkage within 90 seconds at 150°C. The heat shrink tube has the characteristic that when a tube is artificially expanded and then rapidly cooled to produce a finished product during manufacturing, and heat is applied to the finished product, it shrinks back to the state before artificial expansion. The complete shrinkage of the heat shrink tube means shrinking from the artificially expanded finished product state back to the state before artificial expansion.

[0030] Specifically, the composition forming the heat-shrink tube according to the present invention may include a base resin, a flame retardant, a crosslinking agent, a lubricant, other additives, etc.

[0031] The above base resin may include ethylene vinyl acetate (EVA) resin and polyethylene (PE)-based resin, and the ethylene vinyl acetate (EVA) resin may have a melting point (Tm) of 72 to 98°C, and the polyethylene (PE)-based resin may have a melting point (Tm) of 100 to 120°C.

[0032] In particular, the content of vinyl acetate (VA), which is a comonomer of the ethylene vinyl acetate (EVA) resin, may be 4.5 to 28 weight percent based on the total weight of the ethylene vinyl acetate (EVA) resin.

[0033] Here, if the content of the vinyl acetate (VA) is less than 4.5 weight%, the melting point (Tm) of the ethylene vinyl acetate (EVA) resin increases, causing the shrinkage start temperature of the heat shrink tube to rise as well, which may make high-speed shrinkage at low temperatures difficult and reduce the flame retardancy of the heat shrink tube, and if the content of the flame retardant is increased to improve flame retardancy, mechanical properties, heat resistance, etc. may decrease.

[0034] Meanwhile, if the content of the vinyl acetate (VA) exceeds 28 weight%, the modulus of the ethylene vinyl acetate (EVA) resin is reduced, and the shrinkage speed of the heat shrink tube may be reduced.

[0035] The above polyethylene (PE)-based resin may include low-density polyethylene (LDPE) resin, preferably low-density polyethylene (LDPE) resin having a melting point (Tm) of 100 to 110°C and linear low-density polyethylene (LLDPE) resin having a melting point (Tm) of 105 to 120°C, preferably linear low-density polyethylene (m-LLDPE) resin polymerized under a metallocene catalyst.

[0036] Here, the weight ratio of the ethylene vinyl acetate (EVA) resin and the polyethylene (PE) resin may be 4:6 to 6:4. If the weight ratio is less than 4:6, high-speed shrinkage of the heat shrink tube at low temperatures is difficult and flame retardancy may be reduced, whereas if the weight ratio is greater than 6:4, physical properties such as mechanical properties, heat resistance, and flame retardancy of the heat shrink tube may be reduced.

[0037] In addition, when the above polyethylene (PE)-based resin includes both a low-density polyethylene (LDPE) resin having a melting point (Tm) of 100 to 110°C and a linear low-density polyethylene (m-LLDPE) resin having a melting point (Tm) of 105 to 120°C and polymerized under a metallocene catalyst, the weight mixing ratio of these may be 1:3 to 3:1.

[0038] Here, if the weight mixing ratio of the LDPE and m-LLDPE is less than 1:3, the filler loading ability of the composition forming the heat shrink tube is reduced, and physical properties such as mechanical properties, heat resistance, and flame retardancy may be reduced, whereas if the weight mixing ratio is greater than 3:1, physical properties such as mechanical properties, heat resistance, and flame retardancy of the heat shrink tube may be reduced.

[0039] Thus, the heat shrink tube according to the present invention can shorten the time to complete shrinkage to within 90 seconds at 150°C by shrinking at low temperatures, and at the same time, the 2% secant modulus can be improved to 20,000 psi or more, for example, 20,000 to 25,000 psi, thereby securing mechanical properties.

[0040] In addition, by excluding the application of an excessive amount of filler to improve thermal conductivity in order to achieve such high-speed shrinkage, the problem of reduced physical properties such as mechanical properties, heat resistance, and flame retardancy of the heat shrink tube and increased manufacturing costs caused by the application of an excessive amount of filler can be solved.

[0041] The flame retardant may be used by appropriately mixing a bromine-based flame retardant that promotes char formation during combustion and an antimony-based flame retardant that can achieve self-extinguishing properties during combustion, for example, based on 100 parts by weight of the base resin, the content of the bromine-based flame retardant may be 25 to 34 parts by weight and the content of the antimony-based flame retardant may be 12 to 17 parts by weight.

[0042] The above heat shrink tube can be used in a cross-linked state by irradiation crosslinking, and the composition forming the above heat shrink tube may include trimethylopropane trimethacrylate, triaryl isocyanurate, etc. as a crosslinking agent for the above irradiation crosslinking, and the content of the above crosslinking agent may be 2 to 5 parts by weight based on 100 parts by weight of the base resin.

[0043] Here, if the content of the crosslinking agent is less than 2 parts by weight, the degree of crosslinking is insufficient, which can significantly reduce the mechanical strength and insertion workability of the heat shrink tube, whereas if it exceeds 5 parts by weight, the initial crosslinking reaction rate increases rapidly, resulting in a high degree of crosslinking, which makes it impossible to perform the expansion process, which is part of the heat shrink tube manufacturing process.

[0044] The above lubricant performs the function of improving compatibility between the base resin and flame retardants, other additives, etc., and may include, for example, stearic acid lubricants, amine-based lubricants, etc., and the content of the above lubricant may be 0.5 to 5 parts by weight based on 100 parts by weight of the base resin.

[0045] The above other additives may additionally include antioxidants, hydrolytic agents, carbon black, UV inhibitors, processing aids, heat stabilizers, antistatic agents, coupling agents, pigments, etc., depending on the use of the heat shrink tube, and the content of the above other additives may be 7 to 15 parts by weight based on 100 parts by weight of the base resin.

[0047] [Example]

[0049] 1. Preparation Example

[0052] With the components and content listed in Table 1 below, the mixture was mixed using a kneader at 130°C for 15 minutes, then extruded through a 45 mm extruder at a die setting of 150°C at a speed of 20 mpm, followed by irradiation crosslinking, and finally, a heat shrink tube was manufactured through an expansion process. The units of the content listed in Table 1 below are parts by weight.

[0053] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Suzy 1 60 60 40 40 Suzy 2 40 45 40 Suzy 3 40 Suzy 4 40 40 45 60 40 Suzy 5 20 15 15 20 Suzy 6 100 40 Flame retardant 1 28 28 28 28 28 28 28 28 Flame retardant 2 14 14 14 14 14 14 14 14 Bridge 2.5 2.5 2.5 2.5 2.5 2.5 2.5 2.5 lubricant 1.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 Other additives 9 9 9 9 9 9 9 9

[0054] - Resin 1: Ethylene vinyl acetate resin (Vinyl acetate content: 4%; Melting point: 99℃)

[0055] - Resin 2: Ethylene vinyl acetate resin (Vinyl acetate content: 28%; Melting point: 72℃)

[0056] - Resin 3: High-density polyethylene resin (Melting point: 130℃)

[0057] - Resin 4: Low-density polyethylene resin (Melting point: 106℃)

[0058] - Resin 5: Linear low-density polyethylene polymerized under a metallocene catalyst (melting point: 105℃)

[0059] - Resin 6: Polyolefin elastomer (Melting point: 73℃)

[0060] - Flame Retardant 1: Brominated Flame Retardant

[0061] - Flame Retardant 2: Antimony-based Flame Retardant

[0062] - Crosslinking agent: Trimethylolpropane trimethacrylate (TMPTMA)

[0064] 2. Evaluation of physical properties

[0066] 1) Evaluation of room temperature tensile strength and elongation

[0067] The tensile strength and elongation of the heat shrink tube were measured at room temperature at a speed of 250 mm / min according to the standard ASTM 2671. Here, the tensile strength must be at least 1.05 kgf / mm² and the elongation must be at least 250%.

[0068] 2) Evaluation of tensile strength and elongation after heating

[0069] After being left at 150°C for 240 hours, the tensile strength and elongation of the heat shrink tube were measured at a speed of 250 mm / min according to standard ASTM 2671. Here, the tensile strength must be at least 1.02 kgf / mm² and the elongation must be at least 200%.

[0070] 3) Modulus Evaluation

[0071] The 2% secant modulus was measured at room temperature at a speed of 25 mm / min according to standard ASTM D882. Here, the 2% secant modulus must be between 20,000 psi and 25,000 psi.

[0072] 4) Flame Retardancy Evaluation

[0073] According to the ISO-6722 standard, the angle between the burner and the heat shrink tube specimen was fixed at 45°, and a flame was applied 5 times for 15 seconds each in a vertical position to evaluate whether self-extinguishing occurred within 30 seconds.

[0074] 5) Contractility evaluation

[0075] Heat-shrink tube specimens (tube specimens cut to a length of 3 cm) were placed in a 150°C convection oven to heat-shrink them. After removing the specimens after 30, 60, 80, 100, and 120 seconds, respectively, they were immersed in room-temperature cooling water to remove residual heat. The outer diameter was then measured, and if it was the same as the outer diameter before the expansion process, it was evaluated as having undergone complete shrinkage. The time required for complete shrinkage in a 150°C convection oven must be 90 seconds or less.

[0077] The evaluation results of the above physical properties are as described in Table 2 below.

[0079] Examples Comparative example 1 2 3 1 2 3 4 5 Tensile strength (kgf / mm²) 2.551 2.321 2.492 2.142 1.502 2.209 1.944 2.841 Growth rate (%) 620.45 600.67 610.57 563.87 506.64 622.23 625.85 550.02 Tensile strength after heating (kgf / mm²) 2.418 2.284 2.459 2.025 1.92 2.113 2.337 2.64 Elongation rate (%) after heating 592.3 580.64 591.8 570.33 562.4 521.36 569.61 525.55 Modulus (psi) 24,400 20,554 23,214 28,200 11,150 14,450 17,450 25,900 flame retardant pass pass pass pass fail pass pass fail Contractility (sec) 60 60 60 120↑ 60 60 80 100

[0080] As described in Table 2 above, the heat shrink tubes of Examples 1, 2, and 3 according to the present invention were found to have excellent room temperature mechanical properties, heat resistance, flame retardancy, etc., and the time until the shrinkage is completed was only 60 seconds due to high-speed shrinkage caused by a low shrinkage initiation temperature and a high modulus.

[0081] On the other hand, the heat shrink tube of Comparative Example 1 has a 2% secant modulus that exceeds the standard value of 25,000 psi, and due to excessive semi-rigidity, the time taken to complete shrinkage when evaluated in a 150°C convection oven exceeds 90 seconds, so it does not satisfy the high-speed shrinkage standard.

[0082] The heat shrink tube of Comparative Example 2 has a 2% secant modulus of less than the standard value of 20,000 psi, so it lacks semi-rigid properties and is vulnerable to scratch and wear resistance, resulting in relatively poor protection of the internal product. In addition, it was confirmed that the flame retardancy does not meet the standard.

[0083] The heat shrink tubes of Comparative Examples 3 and 4 have a 2% secant modulus of less than the standard value of 20,000 psi, so they lack semi-rigidity and are susceptible to scratch and wear resistance, resulting in relatively poor protection of the internal product.

[0084] The heat shrink tube of Comparative Example 5 has a 2% secant modulus exceeding the standard value of 25,000 psi, and due to excessive semi-rigid properties, the time required for complete shrinkage during shrinkage evaluation in a 150°C convection oven exceeds 90 seconds, failing to satisfy the high-speed shrinkage standard. In addition, it was confirmed that flame retardancy was significantly reduced. Explanation of the symbols

[0085] 100 : Heat shrink tube

Claims

Claim 1 It comprises ethylene vinyl acetate (EVA) resin and polyethylene (PE)-based resin as base resins, wherein the ethylene vinyl acetate (EVA) resin has a melting point (Tm) of 72 to 98 And, the above polyethylene (PE) resin has a melting point (Tm) of 100 to 120 A heat shrink tube having a 2% secant modulus of 20,000 to 25,000 psi. Claim 2 A heat shrink tube according to claim 1, characterized in that the content of vinyl acetate (VA), which is a comonomer of the ethylene vinyl acetate (EVA) resin, is 4.5 to 28 weight% based on the total weight of the ethylene vinyl acetate (EVA) resin. Claim 3 In claim 1 or 2, the polyethylene (PE) resin has a melting point (Tm) of 100 to 110 Phosphorus low-density polyethylene (LDPE) resin with a melting point (Tm) of 105 to 120 A heat shrink tube characterized by containing linear low-density polyethylene (LLDPE) resin. Claim 4 A heat-shrinkable tube according to claim 3, characterized in that the linear low-density polyethylene (LLDPE) resin comprises a linear low-density polyethylene (m-LLDPE) resin polymerized under a metallocene catalyst. Claim 5 A heat shrink tube according to claim 4, characterized in that the weight ratio of the low-density polyethylene (LDPE) resin and the linear low-density polyethylene (m-LLDPE) resin polymerized under the metallocene catalyst is 1:3 to 3:

1. Claim 6 A heat shrink tube according to claim 1 or 2, characterized in that the weight ratio of the ethylene vinyl acetate (EVA) resin and the polyethylene (PE)-based resin is 4:6 to 6:

4. Claim 7 A heat shrink tube according to claim 1 or 2, characterized by comprising 25 to 34 parts by weight of a bromine-based flame retardant and 12 to 17 parts by weight of an antimony-based flame retardant based on 100 parts by weight of the base resin. Claim 8 A heat shrink tube according to claim 1 or 2, characterized by comprising 2 to 5 parts by weight of a crosslinking agent of trimethylopropane trimethacrylate or triaryl isocyanurate based on 100 parts by weight of the base resin. Claim 9 A heat shrink tube according to claim 1 or 2, characterized by comprising, based on 100 parts by weight of the base resin, 0.5 to 5 parts by weight of a lubricant, and 7 to 15 parts by weight of one or more other additives selected from the group consisting of an antioxidant, a hydrolytic inhibitor, carbon black, a UV inhibitor, a processing aid, a heat stabilizer, an antistatic agent, a coupling agent, and a pigment.

Citation Information

Patent Citations

  • High-speed railway ballastless track steel bar insulating heat-shrinkable tube and production method thereof

    CN105602079A

  • Heat recoverable coextruded articles

    KR1019930009044B1

  • Hollow extrusion molded article, crosslinked product thereof, heat-shrink tube, and layered heat-shrink tube

    WO2019097874A1